Effect of consumption heated oils with or without dietary cholesterol on the cevelopment of atherosclerosis - Che Idris, Che Anishas; Sundram, Kalyana; Abdull Razis, Ahmad Faizal (MDPI, 2018)
Heating oils and fats for a considerable length of time results in chemical reactions, leading to the aggravation of a free radical processes, which ultimately contributes to atherosclerosis. Our study focused on elucidating the effect of feeding heated oils with or without dietary cholesterol on the development of atherosclerosis in rabbits. We heated palm olein and corn oil at 180 °C for 18 h and 9 h per day, respectively, for two consecutive days. Next, 20 male rabbits were divided into four groups and fed the following diet for 12 weeks: (i) heated palm olein (HPO); (ii) HPO with cholesterol (HPOC); (iii) heated corn oil (HCO); and (iv) HCO with cholesterol (HCOC). Plasma total cholesterol (TC) was significantly lower in the HCO group compared to the HCOC group. Atherosclerotic lesion scores for both fatty plaques and fatty streaks were significantly higher in the HCO and HCOC groups as compared to the HPO and HPOC groups. Additionally, fibrous plaque scores were also higher in the HCO and HCOC groups as compared to the HPO and HPOC groups. These results suggest that heated palm oil confers protection against the onset of atherosclerosis compared to heated polyunsaturated oils in a rabbit model.